Analysis Effectiveness of the Internal Control System in Detecting Fraud (Study at PT Arminareka Perdana Group) - Mudzakar, Richan Nurhasan; Karsam, Karsam; Paryanti, Atik Budi (Dinasti Publisher, 2026)
This study analyzes the effectiveness of the internal control system in detecting fraud at PT Arminareka Perdana Group. Based on the COSO framework and Social Control Theory, internal control is positioned not only as a governance mechanism but also as a formal social control instrument that shapes ethical behavior and organizational compliance. Using a quantitative approach with PLS-SEM, data were collected from employees involved in financial supervision and operational control. The findings indicate that effective implementation of control environment, risk assessment, control activities, information and communication, and monitoring strengthens fraud detection through structured procedures, segregation of duties, transparent reporting, and continuous evaluation. Internal control contributes to building an accountable organizational culture and supports early identification of irregularities. The novelty of this research lies in integrating COSO-based internal control with Social Control Theory to explain fraud detection from structural and behavioral perspectives, offering strategic insights for strengthening governance and fraud risk management.